Exotic naturalized flora of continental Portugal – A reassessment - Freitas, Helena; Domingues de Almeida, João (Botanica Complutensis, 2006)
Six years after our last study on the exotic naturalized flora of continental Portugal, we present a reassessment. In 1999, we have considered the existence of 500 exotic species of vascular plants (invasive or more or less naturalized). From 1999 until now 64 new plant species records were added (12.8 % more), attaining now a total number of 564 taxa (including, as in precedent works, species, subspecies and some hybrids), belonging to 113 families.